A semiótica dos memes autodepreciativos - Pádua, Camila Giovanelli Sampaio (2022)
The dissertation proposes, through semiotic analysis, a study of self-deprecating gender memes, considering that the imagistic signs of extreme importance for the understanding of mental health issues can be expressed and even have some relief when put under the perspective of memes that are conveyed on modern social networks. Before following this path, there is a contextualization, given the current and unexpected scenario of the COVID-19 Pandemic that has been plaguing the entire world for almost two years